High-efficiency silicon solar cells designed on experimentally achieved nano-engineered low-reflective silicon surface - Zumahi S.M.A.-A.; Basher M.K.; Arobi N.; Rahman M.M.; Tawfeek A.M.; Akand M.A.R.; Rahman M.M.; Nur-E-Alam M.; Hossain M.K. (Springer, 2025)
We explore the design and optimization of high-efficiency solar cells on low-reflective monocrystalline silicon surfaces using a personal computer one dimensional simulation software tool. The changes in the doping concentration of the n-type and p-type materials profoundly affects the generation and recombination process, thus affecting the conversion efficiency of silicon solar cells. To enhance solar cells' performance, copper nanoparticle (Cu-NP) assisted surface texturization has been employed on the silicon surface with resistivity 1?3.cm. The surface texturization assists in reducing the surface reflection of silicon by around 0.65%. The doping concentration and the layer thicknesses of a solar cell are optimized and found that 1 ? 1014cm?3 doping concentration at three different thicknesses (5, 10, and 15?m) of the n-type region exhibit the maximum solar cell conversion efficiency of around 26.19%. The optimized design solution shows the best output parameters namely open-circuit voltage (Voc) around 0.749V, short circuit current (Isc) about 3.987 A, and a fill factor of 26.19% that can be potentially useful for the fabrication of high-efficiency solar cells. ? The Author(s), under exclusive licence to The Optical Society of India 2024.